Comparative Study of Cytology and Histopathology of Cervical Lesion in VIA Positive Patients in Mymensingh - Ansari, Nazma Parvin; Rahman, AJE Nahar; Saleh, AFM; Shahida, SM (Community Based Medical Journal, 2015)
Cervical cancer is the second most frequent type of cancer and leading cause of mortality among women worldwide. More than eighty eight percent deaths from cervical cancer occur in developing countries and by 2030, it will be at least ninety eight percent. In developed countries, the cases and deaths have declined markedly due to their extensive screening programs. The present study was undertaken to assess precancerous and cancerous cervical lesion by cytology and their comparison with histopathology in VIA positive cases. This descriptive, cross-sectional type of observational study was carried out in the Department of Pathology, Mymensingh Medical College in collaboration with the Department of Gynecology and Obstetrics, Mymensingh Medical College Hospital, during the period of July 2012 to June 2013. Study was carried out among 160 VIA positive patients and selected by non-random judgment sampling from the colposcopy clinic. Histological findings revealed that the most common age group affected by different types of cervical lesions is 30 – 39 years. It also revealed that squamous cell carcinoma (SCC) was very much common in age group 40-49 years. The statistical value of accuracy, sensitivity and specificity of Pap smear cytology test and histopathology yielded some important directives. The sensitivity values of Pap smear cytology was found 87.50%. The accuracy of the Pap smears in this study was 88.13%. The present study show significant relationship between cytological test with histopathological diagnosis. However cytology testing is not suitable as a single test. In conclusion, it can be stated that combination of cytology (Pap smear) and histopathology would ultimately be more useful. CBMJ 2015 July: Vol. 04 No. 02 P: 35-40